Spatio-Statistical Analysis of Rainfall and Temperature Distribution, Anomaly and Trend in Nigeria - Elisha Ademola Adeleke; Eniola Aminat Orebayo (Geosfera Indonesia, 2020)
This study aims to examine the variability of rainfall and temperature based on spatio-statistical analysis. Data for the study was gotten from the Nigerian Meteorological Agency and subjected to statistical analysis using mean, standard deviation, time series analysis, t-test and correlation. The results of the study revealed that the mean rainfall in the area is 108.6 mm, mean temperature is 28o C and mean sunshine is 4.7 hours. The result further revealed that mean onset date in the state is 13th march, mean cessation date is 10th October while the mean length of rainy season is 223 days. The result also showed that rainfall anomaly index in the area ranged between -2.12 and 2.28 while temperature anomaly ranged between -2.31 and 1.73. The correlation coefficient showed that cessation (0.408) and Length of rainy season (0.406) is significantly related to rainfall, sunshine hours (0.380) and Average temperature (0.867) is significantly related to minimum temperature, sunshine hours (-0.389) and average temperature (0.749) is significantly related to maximum temperature while onset (-0.642) and cessation (0.509) is significantly related to length of rainy season. However,there is a significant difference in onset dates, cessation dates and length of rainy season in the area. The area is experiencing a significant increase in temperature, rainfall and sunshine hours and recommends that more tress should be planted in the area and Nigerian meteorological agency should also inform farmers about the onset of the rains so as to help the farmers prepare for the planting season. Keywords: Climate; Rainfall; Anomaly; Temperature; Cessation; Onset Copyright (c) 2020 Geosfera Indonesia Journal and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License